The case of using antiangiogenic agent – plasmide vector psFLT and radiochemotherapy in locally advanced vulvar cancer - Panek, Grzegorz; Gawrychowski, Krzysztof; Bidziński, Mariusz; Krynicki, Ryszard; Małecki, Maciej (Menopause Review/Przegląd Menopauzalny, 2005)
This is a case report documenting a successful use of antiangiogenic agent- plasmide vector psFLT with successive chemo-radiotherapy and radical surgery in patient with primarily unoperable invasive carcinoma of the vulva. After 3 courses of subcutaneous injection of 30 micrograms of Plasmide vector psFLTa significant reduction of the tumor size was obtained. Subsequently chemo-irradiation was 5-Fluorouracil and Mitomycin-C was carried out resulting in complete clinical regression of the tumor. Radical vulvectomy and inguino-femoral limphadenectomy was performed 6 weeks after completion of chemo-irradiation. Microscopic examination of the specimen revealed a complete eradication of the malignant tissue. The case demonstrates a significant potential of antiangiogenic therapy combiened with chemo-irradiation for locally advanced carcinoma of the vulva. This experimental method of treatment deserves further investigation.